Enhanced visible−light photocatalytic performance of CdS/Zn1−xCdxWO4 composites prepared by a facile protocol. Issue 9 (15th June 2020) - Wu, Yadong; Luo, Ni; Xie, Ruishi
Abstract: Low toxicity and high photocatalytic activity are imperative for the application of semiconductors to environmental remediation. Herein, CdS/Zn1− x Cd x WO4 composites were designed and successfully synthesized by a facile approach. The phase, morphology, light absorption ability, photoactivity, fluorescence, and photoelectrochemical properties of the composites were systematically investigated. The CdS/Zn1− x Cd x WO4 composites exhibited better photocatalytic activity for the degradation of methyl orange than CdS. Kinetic investigation indicated that the photocatalytic process follows a pseudo−first−order kinetic model. Benefitting from the synergistic effects of ion doping and heterostructure construction, the CdS/Zn1− x Cd x WO4 composites delivered excellent visible−light photocatalytic performance. This study is potentially applicable to hybrid nanostructures used in wastewater treatment and related applications.